MODERASI ISLAM: DARI KONSEP MENUJU IDENTITAS - Fadhliah Mubakkirah (Fakultas Syariah Institut Agama Islam Negeri Palu, 2018)
This paper seeks to present spirit as well as the concept of moderation in Islam to realize the identity and identity of Muslims in their daily lives. There are three styles of expressing Islam namely Left Extremist, Right Extremist and Wasathiyyah. Moderation is taken from this word, wasathiyyah. Moderation of Islam is a concept that teaches not to be extreme, radical, and excessive in religion. This is a characteristic of the Islamic religion. Islam always takes the